Ndebele forced removals, migration, and human-nature relations in Colonial Buhera, Zimbabwe: 1925 - 1980 - Hazvineyi, Lloyd (My University, 2023)
The thesis adopts an interesting angle in socio-environmental history in exploring the past of the Ndebele-speaking Gwebu people of Buhera. It foregrounds the location of agency (finding it and exploring how it worked) in both agricultural practices and the conservation of natural resources after this group were compelled to leave their existing homes in Matabeleland in 1925 and then survived (and thrived at times) up to 1980.
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Colonisation; Ndebele-speaking Gwebu people; Migrations